From Topic Boundaries to Omission : New Research on Interpretation - Metzger, Melanie (Studies in interpretation (Washington, D.C.), 2005)
"When Richard Medugno and his wife Brenda learned in 1993 that their 17-month-old daughter Miranda was deaf, they grieved, as many hearing parents do. Soon, however, Medugno seized hold of the need to take positive action for Miranda. Deaf Daughter, Hearing Father recounts the remarkable story of their journey together during the first fourteen years of her life."